Philosophical Essence Of The Development Of Moral Values (Zien Journal of Social Sciences and Humanities, 2024)
The article scientifically studies the widespread development of moral values, which are an important part of human life, among the peoples of the world today, and the important role of philosophical worldview and factors in this process.